Evaluasi Pertumbuhan dan Produksi Padi Gogo Haploid Ganda Toleran Naungan dalam Sistem Tumpang sari - Priatna Sasmita; Bambang S. Purwoko; S. Sujiprihati; I. Hanarida; I. S. Dewi; M. A. Chozin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
Three doubled haploid (DH) upland rice lines obtained from anther culture having good agronomic and shade tolerant traits were planted in an intercropping with maize. Their monoculture systems were also included. Those lines were GI-8, IG-19, and IW-56. Jatiluhur was also treated similar as shade tolerant control cultivar. The experiment was arranged in randomized complete block design with three replications. The treatments consisted of eight intercropping systems, four monoculture systems of rice, and two monoculture systems of maize. The result showed that all of tested DH lines were consistently shade tolerant under intercropping condition. The characteristics was represented by similar growth and grain yield with Jatiluhur under intercroping system. The highest grain yield was 2.49 t/ha resulted by GI-8 and IG-19 lines at the time that Jatiluhur was 2.36 t/ha. The intercropping of DH lines with maize also showed the Land Equivalent Ratio (LER) =1.33-1.58, while Jatiluhur LER = 1.25-1.28, indicating that agronomically they were more advantageous than those in the monoculture system. Key words : Doubled haploid,, intercropping system, shade tolerant lines